2018
DOI: 10.1097/j.pain.0000000000001190
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms of neuropathic pain: comparison of sensory phenotypes in patients and human surrogate pain models

Abstract: As an indirect approach to relate previously identified sensory phenotypes of patients suffering from peripheral neuropathic pain to underlying mechanisms, we used a published sorting algorithm to estimate the prevalence of denervation, peripheral and central sensitization in 657 healthy subjects undergoing experimental models of nerve block (NB) (compression block and topical lidocaine), primary hyperalgesia (PH) (sunburn and topical capsaicin), or secondary hyperalgesia (intradermal capsaicin and electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 61 publications
3
65
0
Order By: Relevance
“…Pinprick hyperalgesia was indicated by a decreased MPT in the secondary area of hyperalgesia. This gain of function sign is similar to findings after the application of other human surrogate models of central sensitization (e.g., high-frequency stimulation and intradermal capsaicin injections) (Vollert et al, 2018), and as described in a cluster of patients presenting mainly with mechanical hyperalgesia (Baron et al, 2017;Vollert et al, 2017…”
Section: Increased Pinprick Sensitivity In the Area Of Secondary Hysupporting
confidence: 86%
“…Pinprick hyperalgesia was indicated by a decreased MPT in the secondary area of hyperalgesia. This gain of function sign is similar to findings after the application of other human surrogate models of central sensitization (e.g., high-frequency stimulation and intradermal capsaicin injections) (Vollert et al, 2018), and as described in a cluster of patients presenting mainly with mechanical hyperalgesia (Baron et al, 2017;Vollert et al, 2017…”
Section: Increased Pinprick Sensitivity In the Area Of Secondary Hysupporting
confidence: 86%
“…Previous studies reported cold sensation loss in 40% of polyneuropathy, 63% of postherpetic neuralgia, 50% of peripheral nerve injury and 49% of central pain patients (Maier et al, 2010). In various multi-centre studies, QST was validated for the assessment of all known sensory fibre classes, including non-noxious and noxious cold-mediating fibres (Rolke, Baron et al, 2006;Vollert et al, 2018Vollert et al, ,2017. QST is a psychophysical test procedure, which relays on patients' compliance and preserved cognitive function.…”
Section: Ceps Into Small-fibre Function Assessment?mentioning
confidence: 99%
“…In fact, these clusters presented similar patterns to those induced by neuropathic surrogate models in healthy volunteers. 17 The exact stratification algorithm was not applied in clinical trials, yet but responders of recent studies can be tentatively assigned to each cluster: the sodium channel blocker oxcarbazepine showed significant pain relief in a subgroup of patients with an irritable nociceptor phenotype (cluster 2), whereas in the remaining group, there was no effect. 6 Another study indirectly hypothesized that patients with sensory loss (cluster 1) had good response to opioids.…”
Section: Introductionmentioning
confidence: 99%